Licorice Compound Traditional Syrup: Formulation and Development of Analysis Method - Behnaz Keramatian; Leila Ara; Homa Hajimehdipoor* (Iranian Society of Pharmacognosy, 2022)
Background and objective: Glycyrrhiza glabra L. (licorice) is one of the most important medicinal plants for respiratory disorders. It is used alone or in combination with other species. In the present investigation, an herbal syrup containing licorice, fennel, and fig was formulated according to Iranian traditional medicine prescriptions and glycyrrhizic acid content of the syrup was quantified using a validated HPLC method. Method: Traditional syrup was prepared by decocting the mixture of licorice: fennel: fig (20, 8, 62.5 g in 100 mL). It was filtered and concentrated. Sugar was used in the syrup (40%). Quality control tests were performed and glycyrrhizic acid content of the syrup was determined using an HPLC method. The method was verified according to verification parameters, as well. Accelerated stability tests were carried out during 6 months in 40 °C. Results: The prepared syrup was brown colored with fennel odor and sweet taste. The pH, viscosity, dry residue and density were 5.13, 134.8 cP, 51.43%, 1.10 g/cm3, respectively. Glycyrrhizic acid content was 1.99 mg/mL. The HPLC method was valid according to specificity, linearity (9.3-27.9 µg/mL, r2: 0.9972), intra-day precision (RSD≤1.71%), inter-day precision (RSD: 3.31%), instrument precision (RSD: 0.82%), recovery (95.6%), LOD (1.48 µg/mL) and LOQ (4.49 µg/mL). Conclusion: The prepared syrup with suitable physicochemical and microbial characteristics is a proper candidate for producing at industrial scale after further invivo and clinical studies. Moreover, the HPLC method can be used as a validated method for quality control of the syrup.